ANALISIS USAHA PUKAT CINCIN (PURSE SEINE) PADA KM. DOA RESTU-01 DI PERAIRAN GORONTALO UTARA, GORONTALO - Hery Choerudin; Rahmat Muallim; Sadri Sadri; Eli Nurlaela; Danu Sudrajat; Jerry Hutajulu (Buletin Jalanidhitah Sarva Jivitam, 2022)
This research took place from July 2019 to June 2020 at the Gentuma Fish Landing Port, North Gorontalo and MV. Doa Restu-01. The study of financial analysis of new boats within one year provides information to the government and the community as an effort to increase fishermen's income. This study aims to determine the feasibility analysis of purse seine vessels in the waters of North Gorontalo. The data taken in the form of primary and secondary data. The data in the analysis uses descriptive analysis and quantitative analysis as well as financial analysis in the form of Profit-Loss (Income Statement), Benefit Cost Ratio (BCR), Break Even Point (BEP), Payback Period (PP) and Return Of Investment (ROI). The results show that the ring trawling effort at Gentuma meets the requirements and deserves to be continued. The results of the calculation of business feasibility in the purse seine fishing business of MV. Doa Restu-01 based on the projected profit and loss (R/L) the profit earned for 1 year is Rp. 113.856.050,-, the cost benefit ratio (B/C ratio) 1.10, Payback Period (PP) 9.61 years, income on investment (ROI) 10.40%, Break Even Point (BEP) unit 68,385 kg and Break Even Point (BEP) price Rp.965,499,137,-